An urgent need for studies of the late effects of SARS-CoV-2 on the cardiovascular system - Maleszewski, J. J.; Young, P. M.; Ackerman, M. J.; Halushka, M. K. (Circulation, 2020)
There is likely a diverse set of cardiovascular effects of COVID-19 that will be seen and it is essential to calculate each population`s risk and understand their time courses. It would be unwise to have the tail wag the dog on policy decisions and/or predictions of long-term needs of the health care system where extremely rare outcomes guide the overall approach to the disease. We must properly gauge the frequency of late cardiovascular events from much larger and robust data sources. Ultimately, there is a need to balance the long-term societal COVID-19 health risks with other considerations of individual physical, mental, and emotional health.